DESIGN MID TEST II OF MATH MATERIALS BASED ON HIGHER ORDER THINKING SKILL (HOTS) TAKSONOMI BLOOM REVISION ON CLASS V - Muhammad Subhan (Dharmas Education Journal (DE_Journal), 2020)
The reality that happened in the field was that not all of the test questions made referred to HOTS. Lack of availability of HOTS-based questions causes students to be less trained in developing higher order thinking skills. There are six kinds of Revision of Bloom's taxonomy purpused by Lorin Anderson and David Krathwohl (2001) : C1 knowing, C2understanding, C3aplying, C4 analyzing, C5 evaluating, and C6 creates creating. The test questions classified as HOTS are C4 analyzing, C5 evaluating, and C6 creating. This research is clasified as research and development (R & D) developed by Gall, J. P., & Borg, (2003) namely finding Potentials and Problems, Data Collection, Product Design, Design Validation, and Design Revision. In this study, the product developed was the Middle Semester Assessment test questions on the Mathematics content of class V. The results of the validity were determined by 3 validators using observation sheets. The validity of this question is seen from the suitability of content, construction, and language obtained from validator I getting a score of 81.17% with very valid criteria, validator II getting a score of 77.25% with valid criteria, and validator III getting a score of 94.22% with very valid criteria, with reliability 0,680 (Good).